Effects of inspiratory muscle training with progressive loading on respiratory muscle function and sports performance in high-performance wheelchair basketball athletes: A randomized clinical trial - Antonelli, C. B. B.; Hartz, C. S.; da Silva Santos, S.; Moreno, M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To evaluate the effects of inspiratory muscle training associated with interval training on respiratory muscle strength and fatigue and aerobic physical performance (PP) in high-performance wheelchair basketball athletes. Methods: Blinded, randomized clinical trial with 17 male wheelchair basketball players, randomized into control group (CG; n?=?8) and training group (TG; n=9). Respiratory muscle strength was evaluated by measuring maximal inspiratory and expiratory pressures (MIP and MEP), aerobic PP by the Yo-Yo test for wheelchair, and recovery of inspiratory muscle fatigue was assessed at 1, 5, 10, and 15 minutes after exercise test. TG performed inspiratory muscle training protocol with incremental loading for 12 weeks with 50%, 60%, and 70% of MIP, while CG performed with load 15% of MIP. Results: After training period, CG presented a significant increase in MIP and MEP (P=.05), with no change in aerobic PP (P=.05). TG showed a significant increase for all variables (=.05). MIP showed a large effect size for CG (1.00) and TG (1.35), while MEP showed a moderate effect for CG (0.61) and TG (0.73); distance covered had a moderate effect size for TG (0.70). For recovery of inspiratory muscle strength, CG did not present differences, while TG recovered in 10 minutes (=.05), representing 87% of the pretest value. Positive and significant correlation between MIP and distance (.54; P=.05) was observed. Conclusion: Inspiratory muscle training protocol with progressive loading was more effective for increasing aerobic PP and maximal inspiratory strength recovery.